Does the concept of apprenticeship still have relevance as a model of skill formation and vocational learning in contemporary society? - Pattayanunt, Suwimon [Verfasser] (My University, 2009)
"This article analyses the importance of apprenticeship systems in the current contexts of the UK and Germany. It discusses the policy and practice of apprenticeship in connection with skills formation and vocational learning. It argues that despite its declining popularity, apprenticeship continues to play a role in contemporary education policy with possibilities for progress and improvement. However, its practicality and feasibility is dependent on policies which are influenced by the different national socio-political, economic, and educational contexts. Indeed, the reason why the UK's attempts to revitalise its apprenticeship system has not been successful is not because apprenticeship is becoming irrelevant, but rather because policy objectives are not consistent with national capacities. If an apprenticeship system is based on strong institutional arrangements and is adaptable to the labour market and its evolving demands, it has enormous potential to produce different types of intermediate-level skills." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.3.1 Qualifikationsverwertung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Berufliche Qualifikation; Berufsbildungspolitik; Humankapital; Qualifikationsverwertung; Arbeitsproduktivität; Mittlere Qualifikation; Internationaler Vergleich; Bundesrepublik Deutschland; Großbritannien